What Blockchain Technology Can Do to Contribute to Waqf - Cory Vidiati; Endang Hendra; Selamet Santoso; Izzul Faturrizky (Fakultas Agama Islam Universitas Wiralodra, 2021)
This article supports decision-makers for the use of blockchain technology in academies and industry in Indonesia, considering its advantages and disadvantages. Like the current Covid 19 pandemic, it is necessary to obtain accurate data in various economic sectors. Islamic economic instruments such as waqf are an important sector, proven to have played a significant role in socio-economy throughout history, as a philanthropic tool and contribute to Islamic civilization. If developed, managed and utilized properly, it can create sustainability for the community. A method that relies on previous literature, this qualitative paper aims to contribute to encouraging the government to use blockchain for waqf. We outline terms and concepts related to how blockchain works and theoretical trust to investigate how blockchain affects the role of trust in waqf transactions. The results using the SWOT framework, we discuss what emerges from blockchain technology in waqf. The conclusion of this study discusses how blockchain can contribute to waqf instruments based on a conceptual framework. We hope to stimulate interest in theory and practice to encourage discussion in this area.